Proceedings of the 2014 Conference on Interaction Design and Children 2014
DOI: 10.1145/2593968.2593971
|View full text |Cite
|
Sign up to set email alerts
|

Emergent dialogue

Abstract: Games for Change (G4C) is a movement and community of practice dedicated to using digital games for social change 1 . However, a common model of persuasion built into most G4C, called Information Deficit, assumes that supporting children to learn facts will result in behavior change around social issues. There is little evidence that this approach works. We propose a model of game play, called Emergent Dialogue, which encourages children to discuss their values during interaction with factual information in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…By performing upgrades, the city can become more sustainable, and by skipping some turns the players allow the structures and upgrades they have chosen to implement, to get their full effect before advancing to the next level. This behaviour thus seems to indicate a more thoughtful design of the city, which matches with Antle's design principles for sustainability games [Antle et al 2015]. These changes in game play are not trivial, as children needed to move away from the traditional competitiveness of passing levels (a so-called traditional mind set of a game-play), to become concerned about spending less money and taking more advantages of the resources from previous constructions.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…By performing upgrades, the city can become more sustainable, and by skipping some turns the players allow the structures and upgrades they have chosen to implement, to get their full effect before advancing to the next level. This behaviour thus seems to indicate a more thoughtful design of the city, which matches with Antle's design principles for sustainability games [Antle et al 2015]. These changes in game play are not trivial, as children needed to move away from the traditional competitiveness of passing levels (a so-called traditional mind set of a game-play), to become concerned about spending less money and taking more advantages of the resources from previous constructions.…”
Section: Discussionmentioning
confidence: 67%
“…As a collaborative group learning activity, M-Enercities motivates players to discuss and decide together how to build a sustainable city, providing exactly the type of social interaction dynamic to foster communication and cooperation as means to learn about sustainability. In fact, according to scholars, sustainable education is all about having meaningful discussions in which multiple perspectives and trade-offs are exchanged by expressing personal values [Antle et al 2015;Fior et al 2010]. In light of how sustainable education should be taught, the M-Enercities game supports learning goals related with factual knowledge about sustainable development, raised awareness for trade-offs and multiple perspectives concerning sustainability, and the role of personal values.…”
Section: Learning Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest designers consider these aspects in their design. Designing strategies to support positive collaborative learning : Although several articles contained collaborative learning activities, most of the collaborative learning activities were limited to sitting and using the AR application together (Barreira et al., 2012; Vate-U-Lan, 2012) or holding a shared tablet to find certain real-world objects and words (Sytwu & Wang, 2016), from which we still could not know how much collaborative learning actually occurred and how equally each learner participated in the learning activity. Previous research has suggested the importance of equal verbal and non-verbal participation in a collaborative learning activity (Antle et al., 2014). We encourage designers leveraging various design strategies (e.g., jigsaw methods) and investigating whether and how these design strategies could support equal and in-depth discussion and effective physical interaction among students as well as the potential influence on students’ learning outcomes. Exploring AR design in various learning contexts : We also noticed a few articles attempted to cover the personalized use of AR applications, for example, learning styles (Hsu, 2017), and the uses of AR applications in various learning contexts (e.g., individual, small groups, classroom; Vate-U-Lan, 2012) and learning groups (e.g., readers with attention deficit hyperactivity disorder and Autism; Lin et al., 2016; Tang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Insights from current educational theory on play and learning indicate that well-designed tabletop games can help to stimulate dialogue around large-scale societal issues such as social class inequality [Carreiro and Kapitulik, 2010], religious tolerance [Roux, 2003], and health education [Bochennek et al, 2007]. Similarly, research in science communication has shown that tabletop games can be effective in raising environmental awareness [Antle et al, 2014;D'Angelo, Pollock and Horn, 2015] , but this has largely involved the creation of bespoke educational games for children, while our aim was to develop a game capable of generating dialogue around global warming for a more general audience.…”
Section: Introductionmentioning
confidence: 99%